Inflationary effects of oil prices and domestic gasoline prices: Markov-switching-VAR analysis - (:unkn) unknown (SPRINGEROPEN, 2015)
The purpose of this study is to contribute to the literature by studying the effects of sudden changes both on crude oil import price and domestic gasoline price on inflation for Turkey, an emerging country. Since an inflation targeting regime is being carried out by the Central Bank of Turkey, determination of such effects is becoming more important. Therefore empirical evidence in this paper will serve as guidance for those countries, which have an inflation targeting regime. Analyses have been done in the period of October 2005-December 2012 by Markov-switching vector autoregressive (MS-VAR) models which are successful in capturing the nonlinear properties of variables. Using MS-VAR analysis, it is found that there are 2 regimes in the analysis period. Furthermore, regime changes can be dated and the turning points of economic cycles can be determined. In addition, it is found that the effect of the changes in crude oil and domestic gasoline prices on consumer prices and core inflation is not the same under different regimes. Moreover, the sudden increase in gasoline price is more important for consumer price inflation than crude oil price shocks. Another finding is the presence of a pass-through effect from oil price and gasoline price to core inflation.
Keywords: Crude oil price; Domestic gasoline price; Consumer price index; Core inflation; MS-VAR model; TIME-SERIES; SHOCKS; MACROECONOMY; IMPACT